CATALYSTS: MECHANISMS, TYPES, AND THEIR INDUSTRIAL APPLICATIONS - Qurbonova Manzura Fardayevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  Catalysts  are  substances  that  accelerate  chemical  reactions  without being consumed in the process. They are fundamental in modern chemical industry, environmental  protection,  and  biological  systems.  This  paper  discusses  the classification of catalysts, their mechanisms of action, and their industrial significance. Additionally, recent advances in nanocatalysis and sustainable catalytic systems are reviewed.